Defining Success in the Commons: Addressing Problem Orientations, Multidimensionality, Norms, and Tradeoffs. Issue 1 (24th August 2020) - Barnett, Allain J.; Partelow, Stefan; Frey, Ulrich; García-Lozano, Alejandro; Mancha-Cisneros, Maria del Mar; Oberlack, Christoph; Ratajczyk, Elicia; Smith, Hillary; Villamayor-Tomás, Sergio; Whitney, Charlotte K.
Commons and social-ecological systems research examines institutional arrangements for governing natural resources to improve social and ecological outcomes. However, no universal definition of success exists. We examine the CPR and SES synthesis literature to identify trends, gaps and challenges for examining success. We address: (1) gaps in the literature, (2) multidimensionality and tradeoffs, and (3) and the link between problem orientation and definitions of success. To do this we conduct a comprehensive review of Large-N studies, meta-analyses and systematic reviews of CPR and SES governance (n = 45). We found seven dimensions of success, corresponding to collective choice, constitutional and operational levels, temporal dimensions, and socio-economic outcomes. Most studies did not address power and tradeoffs, or specify the social groups to whom success would apply. The majority of studies defined success in one dimension, most often demand-side provisioning (e.g., productivity or biodiversity). A regression analysis suggests that studies on rangelands or grasslands, correlative studies, and/or studies of state property systems (i.e., protected areas) were more likely to use fewer dimensions of success. Problem orientations often did not correlate with dimensions of success considered in a study, suggesting that measures of success often cannot adequately address the full suite of problems recognized in synthesis research. This presents a significant challenge for collective action among scholars who aim to develop general knowledge on SES and CPR governance. We discuss exemplary studies that measure success as multidimensional, address power and tradeoffs, and conclude with four recommendations for advancing the analysis of success.